Behavior of concentrically loaded geopolymer-concrete circular columns reinforced longitudinally and transversely with GFRP bars. (15th June 2016) - Maranan, G.B.; Manalo, A.C.; Benmokrane, B.; Karunasena, W.; Mendis, P.
Highlights: Investigation of the circular geopolymer-concrete columns reinforced with GFRP bars. Effect of hoops and spirals reinforcements with different spacing. Behavior of short and slender concrete columns. Evaluation of the load–deformation, confinement efficiency and ductility index. Abstract: The behavior of concentrically loaded geopolymer-concrete circular columns reinforced longitudinally and transversely with glass–fiber-reinforced-polymer (GFRP) bars was investigated. Six full-scale short columns ( L / r  = 8) were cast: one column without transverse reinforcement; three columns with circular hoops spaced at 50 mm, 100 mm, and 200 mm on centers; and two columns with spirals spaced at 50 mm and 100 mm on centers. In addition, two slender columns ( L / r  = 16) transversely reinforced with hoops and spirals both spaced at 100 mm on centers were fabricated. Based on the experimental results, the GFRP bars contributed an average of 7.6% to the overall capacity of the tested columns. The hoop- and spiral-confined slender columns failed at a load equal to 66% and 82%, respectively, of the strength of their counterpart short columns. Irrespective of the tie configuration, the columns with higher volumetric ratios showed better compressive behavior than those with lower volumetric ratios. The ductility and confinement efficiency of the spiral-confined columns were higher than that of their counterpart hoop-confined columns. The tested columns yielded relatively superior compression performance compared to OPC-based concrete columns reinforced with GFRP bars and ties. Further studies dealing with the behavior and slenderness limit in GFRP-reinforced geopolymer concrete slender columns are recommended to increase its uptake in the construction industry.